2020
DOI: 10.3390/min10050393
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Characterization and Chronology of Roman Mortars from the Archaeological Site of Arroyo De La Dehesa De Velasco (Burgo De Osma- Ciudad De Osma, Soria, Spain)

Abstract: This study characterises the mortar materials used in the construction of walls and floors at the Arroyo de la Dehesa de Velasco site, located near the Roman city of Uxama Argaela (the modern Burgo de Osma—Ciudad de Osma, Soria, Spain). Multilayer mortars have been characterised by petrographic, mineralogical (X-ray diffraction and scanning electron microscopy with energy dispersive analyses and geochemical analysis (X-ray fluorescence). Additionally, radiocarbon dating of the mortar binder fraction was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The ANOVA 1-way analysis showed that the variables with significant statistical influence to define these two groups were Al 2 O 3 , K 2 O, SiO 2 , Ba, Cs, Ga, Nb, Rb, Sn (p = 0.00), MgO, Zr (p = 0.001), P 2 O 5 (p = 0.002), Ni (p = 0.003), Br, Sr (p = 0.006), Na 2 O (p = 0.007), and Fe 2 O 3 (p = 0.015). (20.7-35.9%), when compared with the same elements from other studies on roman mortars [8,10,37]. A study on Pompeii mortars [38] found low percentages of CaO (3.81%) and attributed this low content to the high content of volcanic rock fragments as well as to the to the chemical composition of the binder composed by a mixture of lime and clay.…”
Section: Resultsmentioning
confidence: 52%
“…The ANOVA 1-way analysis showed that the variables with significant statistical influence to define these two groups were Al 2 O 3 , K 2 O, SiO 2 , Ba, Cs, Ga, Nb, Rb, Sn (p = 0.00), MgO, Zr (p = 0.001), P 2 O 5 (p = 0.002), Ni (p = 0.003), Br, Sr (p = 0.006), Na 2 O (p = 0.007), and Fe 2 O 3 (p = 0.015). (20.7-35.9%), when compared with the same elements from other studies on roman mortars [8,10,37]. A study on Pompeii mortars [38] found low percentages of CaO (3.81%) and attributed this low content to the high content of volcanic rock fragments as well as to the to the chemical composition of the binder composed by a mixture of lime and clay.…”
Section: Resultsmentioning
confidence: 52%
“…The iron-rich content registered for the coarse plaster layer (typically based on river sand and slaked lime [24]) can be considered a local adaptation and indicates the use of clay-rich materials within the matrix. As shown in previous studies [60,61], the mineralogical characteristic of the plasters can be related to the geographic location, and it can be used to identify the provenance of the raw materials used. We assumed that most of the construction materials used for the plasters coming from Alburnus Maior were obtained from local sources.…”
Section: Discussionmentioning
confidence: 97%
“…Given the fact that the ceramic findings and the wall painting fragments investigated in the current study belong to the exact chronological segment [5], it is possible that the same raw material source locations were used in both cases. As shown in previous studies [60,61], the mineralogical characteristic of the plasters can be related to the geographic location, and it can be used to identify the provenance of the raw materials used. We assumed that most of the construction materials used for the plasters coming from Alburnus Maior were obtained from local sources.…”
Section: Discussionmentioning
confidence: 97%
“…The characterization of these mortars could be used to validate the historical sequential chronology described. Thus, the mortars composition gave us the guidelines to restore and conservate [26] this asset and to evaluate future interventions on these constructive elements. It is worth mentioning that, since the construction of the temple until our days, the city of Quito has been affected by tectonics and earthquakes of great intensity, particularly the one of 1755 known as the "earthquake of Quito", which collapsed the novitiate cupola and its roofs and damaged the masonry of the central nave.…”
Section: Figurementioning
confidence: 99%
“…The characterization of these mortars could be used to validate the historical sequential chronology described. Thus, the mortars composition gave us the guidelines to restore and conservate [26] this asset and to evaluate future interventions on these constructive elements.…”
Section: Figurementioning
confidence: 99%